Merging Transition-Metal Catalysis with Phthalimides: A New Entry to Useful Building Blocks - Yuan, Yu-Chao; Bruneau, Christian; Gramage-Doria, Rafael (Synthesis, 2018)
Phthalimides have found their main application in organic synthesis as protecting groups for primary amines during the multistep synthesis of biologically relevant targets. On the other hand, phthalimide functionalization is rather challenging and it is traditionally associated with the use of over-stoichiometric amounts of environmentally hazardous reagents. In this short review, we describe and discuss how, in the last decades, transition-metal catalysts have provided useful organic building blocks after selective transformation of the phthalimide skeleton in a more efficient and sustainable manner.1 Introduction2 Partial Carbonyl Reduction3 Full Carbonyl Reduction4 Aromatic Ring Reduction5 Five-Membered-Ring Opening6 Conclusion
Keywords: phthalimides; transition metals; catalysis; hydrogenations; fine chemicals